Pemberdayaan Ibu Rumah Tangga Melalui Ekonomi Kreatif Agroindustri Jamur Tiram - Sri Sumarliani; Sri Hastuti (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Women who become housewives make some women only rely on income from their husbands as the head of the family. Meanwhile, women also have a big role in poverty reduction activities through the empowerment of housewives to improve the welfare of their families by carrying out productive business activities. This activity aims to empower housewives to improve the family economy through processed raw oyster mushrooms into one processed product such as chips, noodles, meatballs, oyster mushroom broth that can be consumed by the community and can be optimally developed into preparations with a high selling value. The method used is socialization and awareness that innovation in processed oyster mushrooms through the empowerment of housewives who are members of the oyster mushroom farmer group